Managing Technology: Issues and Options - Kumar Singh, Alok (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Technology, economy and society need to be a tool of renewal or change of existing products, procedures or methods. These changes emerging from being manifested through innovation means that technology is not only innovative, but also prepares a way to further promote innovation. The Bonding Technique raises a special challenge for managers between technology and innovation: the challenge of operating from uncontrolled variables to controlling the development of innovation. It requires some practical freedom to derive ideas of speed of creativity and creativity. Keywords: Leadership, Competition, Murphy's Law, Technology, Economy.